2018
DOI: 10.1097/icu.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Drop instillation and glaucoma

Abstract: Poor eye drop technique is a significant impediment to achieving good control of intraocular pressure in glaucoma. Both mechanical device interventions and educational interventions offer promise to improve patients' technique, but studies with stronger designs need to be done followed by introduction into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 31 publications
3
41
1
1
Order By: Relevance
“…Davis et al reviewed the literature on drop instillation and found reports suggest 6.8-37.3% of patients miss the eye with the drop. 21 None-the-less our patients had a reduction in pressure implying the active ingredient was reaching their eye; at least on the days they were assessed.…”
Section: Discussionmentioning
confidence: 92%
“…Davis et al reviewed the literature on drop instillation and found reports suggest 6.8-37.3% of patients miss the eye with the drop. 21 None-the-less our patients had a reduction in pressure implying the active ingredient was reaching their eye; at least on the days they were assessed.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with glaucoma and ocular hypertension, topical antihypertensive agents are typically the first-line therapy for controlling intraocular pressure. 1,11,16 Persistent elevation of intraocular pressure leads to optic nerve head damage and visual field loss; therefore, proper instillation and adherence to the prescribed therapeutic regimen are vitally important to prevent optic nerve damage and preserve vision. 1,[6][7][8] Prior studies have shown a significant correlation between both non-adherence and poor instillation technique and adverse clinical outcomes such as increased intraocular pressure and visual field loss.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,16 Persistent elevation of intraocular pressure leads to optic nerve head damage and visual field loss; therefore, proper instillation and adherence to the prescribed therapeutic regimen are vitally important to prevent optic nerve damage and preserve vision. 1,[6][7][8] Prior studies have shown a significant correlation between both non-adherence and poor instillation technique and adverse clinical outcomes such as increased intraocular pressure and visual field loss. 8,12,14,22 Studies evaluating self-administration of eye drops in patients with glaucoma have shown that 11-60% are nonadherent to the prescribed therapy, 8,12,14,15,[23][24][25][26] 34-92% use improper instillation technique, 3,8,12-17 7-44% miss the eye completely, 3,12,15,16,27,28 and 18-80% contaminate the tip of the bottle by contacting the eye or periocular tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations